2004
DOI: 10.1046/j.1439-0396.2003.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of stage of lactation, teat position and sequential milk sampling on the composition of domestic cat milk (Felis catus)

Abstract: Milk from 11 domestic shorthair cats (Felis catus; n=7 fed dry low-fat diet, n=4 fed dry high-fat diet) was collected weekly for 6 weeks following parturition, and analysed for total solids (TS), crude protein (CP), fat, lactose and ash. Samples were collected in 1-ml sequential fractions to determine whether within-sampling changes in composition existed Samples of extracted milk fat were also analysed for fatty acid content. Two commercia kitten milk replacers were analysed according to the same procedures u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
0
28
1
Order By: Relevance
“…In species with foregut fermentation, in particular the ruminants, the ingested fatty acids are changed by fermentation, mainly hydrogenated. Every species of monogastric digesters, such as the lion (De Waal et al, 2005), cat (Jacobsen, 2004), pig (Csapó et al, 1996) and primates (Milligan et al, 2008;Osthoff et al, 2009a), and hindgut fermenters, such as the African elephant (Osthoff et al, 2005), seems to have a unique need for certain fatty acids and the milk fat composition may be dictated by a preference for the incorporation of dietary fatty acids or de novo synthesized medium chain (8:0 -14:0) fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…In species with foregut fermentation, in particular the ruminants, the ingested fatty acids are changed by fermentation, mainly hydrogenated. Every species of monogastric digesters, such as the lion (De Waal et al, 2005), cat (Jacobsen, 2004), pig (Csapó et al, 1996) and primates (Milligan et al, 2008;Osthoff et al, 2009a), and hindgut fermenters, such as the African elephant (Osthoff et al, 2005), seems to have a unique need for certain fatty acids and the milk fat composition may be dictated by a preference for the incorporation of dietary fatty acids or de novo synthesized medium chain (8:0 -14:0) fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to DHA and ARA supplementation of human infant formula, these products contained low concentrations of DHA and ARA, compared with human milk. 9 Two studies 10,11 have investigated the fatty acid composition of 4 cat milk replacers, compared with that of domestic cat milk. Both studies 10,11 found that the milk replacers contained no detectable concentrations of DHA.…”
mentioning
confidence: 99%
“…9 Two studies 10,11 have investigated the fatty acid composition of 4 cat milk replacers, compared with that of domestic cat milk. Both studies 10,11 found that the milk replacers contained no detectable concentrations of DHA. Arachidonic acid concentrations ranged from undetectable to 60% of the concentration in cat milk in both studies; 3 of 4 products contained concentrations < 16% of the concentration in cat milk.…”
mentioning
confidence: 99%
“…Several forms of colostrum are produced during the first 24 to 72 hours after birth, after which the composition slowly transforms to mature milk. 9 Lastly, lactose concentrations in cat milk stay relatively constant or increase slightly throughout lactation (Table 21-1). 6,7 Protein concentration then slowly increases throughout lactation to again reach a concentration of about 8%.…”
Section: Composition Of Natural Milkmentioning
confidence: 99%